Clinical effect of stannous fluoride and amine fluoride containing oral hygiene products: a 4-year randomized controlled pilot study - Frese, Cornelia; Wohlrab, Theresa Friederike; Sheng, Liyang; Kieser, Meinhard; Krisam, Johannes; Wolff, Daniela (Scientific reports, 2019)
This 4-year randomized controlled trial (RCT) aimed at investigating whether routine home use of both a SnCl2/AmF/NaF-containing mouth rinse and toothpaste has a preventive effect on oral health. Fifty-four test subjects were examined in biannual intervals. The primary endpoint “dental erosion” was determined by the Basic Erosive Wear Examination (BEWE). The secondary endpoints were “saliva pH”, “dentin hypersensitivity” generated by Visual Analogue Scale (VAS), and “discoloration” measured by the Lobene Stain Index (LSI). A mixed model for repeated measures (MMRM) was used to analyze the primary endpoint “dental erosion”. Primary analysis showed a significant intervention effect of the SnCl2/AmF/NaF-containing test product (p1 = 0.0242). This result was confirmed by two additional MMRM-based sensitivity analyses. Comparison of all models showed “dental erosion” values of the intervention group below values of the control group. Discoloration of the teeth was significantly higher in the intervention than in the control group at all time points. Saliva pH and dentin hypersensitivity were not significantly different between groups over four years. In summary, this RCT is the first to indicate a possible preventive effect of SnCl2/AmF/NaF-containing oral hygiene products on dental erosion over a follow-up period of four years.
Gesehen am 23.10.2019